Pengembangan Media Storyboard DAB (Daily Activity Board) dalam Meningkatkan Keterampilan Bicara Anak Usia 5 -6 Tahun - Anisa Fatimatus Salsabela; Dhian Gowinda Luh Safitri; Suharti Suharti; Melia Dwi Widayanti (Pusat Riset dan Inovasi Nasional, 2026)
This study was motivated by the low speaking skills of children aged 5–6 years in expressing ideas, telling experiences, and using vocabulary coherently during learning activities. This research aimed to develop Storyboard DAB (Daily Activity Board) media and determine its effectiveness in improving the speaking skills of children. This study used the Research and Development (R&D) method with the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this research were 25 children in group B at TK Islam Al-Fatah. Data were collected through expert validation sheets, observation, and pretest–posttest assessments. Data analysis was conducted using the Paired Sample t-test and N-Gain test. The results showed that the Storyboard DAB media was feasible to be used in learning activities. The hypothesis test indicated a Sig. (2-tailed) value of 0.000 < 0.05, which means there was a significant difference between the pretest and posttest results. The N-Gain value of 0.0536 indicates that there was an improvement in children's speaking skills, although it was still categorized as low. In conclusion, Storyboard DAB (Daily Activity Board) can be used as an alternative learning media to help improve the speaking skills of children aged 5–6 years.